Retrospective analysis for valproate screening targets with liquid chromatography–high resolution mass spectrometry with positive electrospray ionization: An omics‐based approach. Issue 5 (13th December 2018) - Mollerup, Christian Brinch; Rasmussen, Brian Schou; Johansen, Sys Stybe; Mardal, Marie; Linnet, Kristian; Dalsgaard, Petur Weihe
Abstract: Liquid chromatography coupled with high‐resolution mass spectrometry (LC–HRMS) is an important analytical tool in the systematic toxicological analysis performed in forensic toxicology. However, some important compounds, such as the antiepileptic drug valproate (valproic acid; VPA), cannot be directly detected with positive electrospray ionization (ESI + ) due to poor ionization. Here we demonstrate an omics‐based retrospective analysis for the identification of indirect screening targets for VPA in whole blood with LC–ESI + –HRMS. Analysis was performed utilizing data acquired across four years from LC–ESI + –HRMS, with VPA results from a quantitative LC–MS/MS method. The combined data with VPA results were split into an exploration set ( n = 68; 28% positive) and a test set ( n = 37; 32% positive). Eight indirect targets for VPA were identified in the exploration set. The evaluation of these targets was confirmed with retrospective target analysis of the test set. Using a combination of two out of the eight indirect targets, we attained a sensitivity of 92% ( n = 12; VPA concentration range: 4.4–29.7 mg/kg) and 100% specificity ( n = 25) for VPA with LC–ESI + –HRMS. VPA screening targets were identified with retrospective data analysis and could be appended to the existing screening procedure. A sensitive and specific screening with LC–ESI + –HRMS was achieved with targets corresponding to the sodium adducts of C7 H14 O3 and C8 H14 O3 . Three chromatographic resolved isomer peaks were observed for the latter, and the consistently most intense peak was tentatively identified as 3‐hydroxy‐4‐en‐VPA. Abstract : Important compounds, such as valproate, cannot be directly detected using positive electrospray ionization LC‐MS. However, retrospective analysis of positive electrospray ionization LC‐HRMS screening data, identified indirect targets for valproate in an exploration set (n = 68, 28% positive). Target analysis using these indirect targets identified valproate with 97% accuracy in a test set ( n = 37, 32% positive).